USING SHORT STORY GAP FILL TO ENHANCE STUDENTS’ LISTENING COMPREHENSION ABILITY - Nur Ekaningsih (Universitas Muria Kudus, 2019)
This research explained how listening comprehension by Short Story Gap Fill improved students’ listening comprehension achievement, observed students’ behavior during listening comprehension class and described the teacher’s Gap Fill technique along with the research. It used Classroom Action Research (CAR) with quantitatively data then analyzed into qualitative. The qualitative data were about students’ interview, while the quantitative data was their scores in pre-test and post-test on listening comprehension. Short Story Gap Fill contained listening comprehension exercises which tend to prove the missing words or phrases on a script of a story or a dialog; they were “pre, while and post-listening which focused on students’ ability to carry out the gap on the listening exercises. This research consisted of two cycles. The findings involved, the third-semester students of the English Department were fascinated by Short Story Gap Fill and immersed in listening comprehension well. However, during the first cycle, there were still 3 from 31 incompletely fulfill the gap in listening comprehension because they could not catch the vocabulary well and less focus. Ultimately, on the second cycle, the students' accomplishment in listening comprehension through this technique improved dramatically on their score of using the same technique. Keywords: CAR, Gap Fill, Listening Comprehension